Macroeconomic variable towards economic growth in Malaysia / Mimi Syahirah Omar - Omar, Mimi Syahirah (2017)
The purpose of conduct this study is to investigate the association and relationship between population, unemployment and export with economic growth in Malaysia. The data collected cover from the year 2006 until 2016 using quarterly data, which consist of 44 data observation. Population, unemployment and export were use as independent variable. Unit root test and diagnostic test were being used to test whether it is stationary or non-stationary. The analyses are conducted using simple linear regression and multiple linear regressions to get the results. Overall this study achieved the research objective and research question where to examine the association and relationship between macroeconomic variables with economic growth in Malaysia. The association were determined based on the result of correlation. The result shows population, unemployment and export are significant at 5%significant level. Meanwhile, relationship were tested by using Multiple Linear Regression technique. In this study, confirmed that population are significant and negative relationship towards economic growth in Malaysia. The result for export are positive significant relationship towards economic growth in Malaysia. Meanwhile, unemployment result shows the insignificant relationship towards economic growth in Malaysia. It means that, the unemployment has no significant effect on Gross Domestic Product in Malaysia.